Product gas distribution and composition from catalyzed gasification of mimosa - Wongsiriamnuay,T. (International Journal of Renewable Energy Research, 2015)
The aim of this study is to analyze the potential of giant sensitive plant or Mimosa for gaseous fuel production by means of gasification process. An experimental study was carried out in a bench scale, fixed bed gasifier with air at atmospheric pressure. Parametric investigation was performed to determine the effect of temperature (600-900°C), collection time (10-110 min) and catalyst to biomass ratio (0.5-2) on product gas yields and composition. Experimental results showed that high temperature favors hydrogen, carbon monoxide and carbon dioxide yield (11, 18 and 24 mol %), while methane was found to follow opposite trend. Production rates of hydrogen and carbon monoxide appeared to increase during volatile releasing step, but decrease during carbonization. With catalyst to biomass ratio of 1, high hydrogen and carbon monoxide concentrations in the product gas (27 and 29 mol%, respectively) were achieved.